Montessori Elder and Dementia Care, and Trauma-Informed Approaches - Bernadette Phillips (University of Kansas, 2023)
According to the World Health Organization, there are currently more than 55 million people living with dementia worldwide, and this figure is expected to triple by 2050. Recent studies suggest that there may be a link between childhood trauma (which refers to exposure to overwhelmingly stressful experiences before the age of 18 years) and the onset of dementia in later life. Therefore, in communities caring for persons living with dementia, some residents may have been exposed to trauma in childhood. Currently, there is an increasing awareness of the negative impact of childhood trauma on later adult health and well-being, and a corresponding recognition of the need for services, including for dementia care, to be trauma-informed. In the last decade, the Montessori Method has become established as a legitimate approach to elder/dementia care. However, it has not yet been examined as a trauma-informed approach. The aim of this paper is to address that gap by (a) highlighting how Maria Montessori took steps to integrate interdisciplinary knowledge of trauma into her Method when she began to understand the potential of childhood trauma to adversely impact adult health and well-being, and (b) outlining how the Montessori Method, when applied to dementia care, incorporates many of the core principles of trauma-informed practice. This paper concludes that the Montessori Method for dementia care has the built-in capacity to be trauma-sensitive and trauma-responsive, but that its ongoing rollout should follow Montessori's lead by specifically integrating knowledge about the neurobiology of trauma into its training programs.